Tata Kota Sumenep Berbasis Teologis sebagai Konstruksi Sosial dalam Mewujudkan Harmoni - Moh. Abu Na'im (IAI Darussalam, 2018)
This study describes the Sumenep Township built by the Somala Penitency having important theological values. The location of Kraton, Alun alun, Mosque and Asta Tinggi is a real manifestation of the pattern of relation Hablum Minal Allah Hablum Minannas, Hablum Minal Alam. By using Peter L Berger's Social Construction theory, it can be seen that the city of Sumenep is a concrete manifestation of the Sumenep Society's faces. Although located within the Section of Madura, but the Sumenep Society has a quite unique difference with other districts. Especially the culture of a society that has a high social harmony. Sumenep is lonely from social conflict. This is backed by his past as a trajectory of various world civilizations that enter through the port of Kalinget. Nevertheless, urban planning as an important symbol is supported by other actors involved in shaping the Sumenep society. The actors can be seen from the minds of people who know the submission in the relationship Bhepa 'Bhebu' Guruh Ratoh. The creations of the three submissions gave birth to